Integrated bathymetric survey of Banate Bay, Iloilo - Cabarles, Raymond C. (Miagao, Iloilo University of the Philippines Visayas, 2016)
Bathymetry is fundamental to the ocean management of a particular body of water, as bottom topography relates to other variables such as salinity, turbidity and sediment profile. This study specifically aimed at determining the largely unknown bathymetry of Banate Bay, Iloilo to explain the process of sedimentation in the bay in relation to river run off and aquaculture discharges. Bathymetric data were collected using a high resolution echo sounder and subsequently processed into-two-and three-dimensional maps for detailed examination. Two-dimensional bathymetric maps revealed that the southwest region of the bay was shallower than the north and northeast regions towards which the sediment deposition was oriented. Three-dimensional bathymetric maps further revealed interesting geologic features typically produced by seismic activities. An old ridge and an fault that cuts across it were of particular interest. The latter was the most prominent feature that was oriented NE-SW. The salinity and turbidity data confirmed the spatial influence of fresh water input, indicating that the rivers largely influenced the physical, chemical and geological dynamics of the bay. This finding was supported by sediment profile, mainly of silt and clay, which were of terrestrial (nearshore) origin. The study findings have non-trivial impacts to the existing management practices in the bay and the coastal areas.
Thesis (M.S. Ocean Sciences) -- Miagao, Iloilo : University of the Philippines Visayas, August 2016.
Keywords: Bathemetry; Banate Bay; Ocean management